(untitled) (Global Journal of Human-Social Science, 2015)
At present tourism has been seriously considered in the national sustainable development strategies of many developing countries and placed on the agenda of many international conferences on Sustainable Development Tourism in a broader sense has existed for a long time in this Hill region of Darjeeling in West Bengal The tourism activities are still in its conventional state not put in the track of modern concept though efforts are being made to give it the real shape under eco-tourism but no avail Sustainable tourism development provides the opportunity to take proactive approaches based on broad participation by stakeholders which would contribute to more effective policies and plans Based on secondary sources literature search and discussions with key stake holders and interaction with the tourist the existing tourists scenario and situation were studied The information collected from different sources has been verified with the field experience Darjeeling receives around 3 5 lakhs domestic tourists annually besides 50 000 foreigners The present study attempt to identify the major issues and challenges of the region regarding its natural resources which can be utilized in a proper scientific manner through a planned natural resource management with active participation of local people and other government and non-government organizations in a sustainable manner The major conclusion that has emerged from the present study is that the overzealous and unplanned growth of tourism and limited infrastructure in the Darjeeling hills of India is identified and it has been suggested that sustainable tourism development should be properly adopted to arrest further environmental decay and encourage a new approach to planning in the region